Development of saponin-based nano emulsion formulation from selected plants to control cotton aphid Aphis gossypii glover - Roonjho, Rehman Abdul (2021)
This study focused on development of saponin based nano-emulsion formulation from 10 locally available medicinal plants to control Aphis gossypii. Saponin was extracted and quantified using HPLC. The results revealed that all plants tested in the study were rich in saponin. However, the highest saponin contents were observed in Porterandia anisophylla (53063 mg/L), Antidesma cuspidatum (42829 mg/L) and Clidemia hirta (42510 mg/L). Plant extracts were further tested for toxicity on A. gossypii through mortality and repellency tests. Based on mortality and repellency tests, C. hirta, Phaleria macrocarpa, P. anisophylla, and A. cuspidatum showed strong pesticidal effects and were selected to be formulated with non-ionic surfactants (Termul 1284, Emersense AM8025 and Tween 80) and oils (rapeseed oil and methyl oleate). The nano-emulsion formulations were successfully developed using ternary phase diagram system. Eleven formulations namely TR3PM, TR3CH, TR3AC, TR3PA, TM1PM, TM1CH, TM2CH, TM3PM, TM3CH, TM3AC and TM3PA (T= Termul 1284, R= Rapseed oil, M= Methyl oleate; PM= P. macrocarpa, CH= C. hirta, AC= A. cuspidatum and PA= P. anisophylla) passed stability tests and further proceeded for physical characterization, results showed that all formulations having particle size ranging from 52.1 to 216.4 nm and fit into nanoemulsion group. The mean zeta potential and mean surface tension of these nanoemulsion formulations ranging from -9.39 to -23 mV and 32.414 to 35.409 mN/m respectively. These 11 formulations were further proceeded to evaluate their toxicity on cotton aphid in laboratory condition and results revealed that after 72 hours the highest mortality percentage was achieved at 10000 mg/L concentration in TR3CH (100%), TR3PM (96%), TR3AC (96%), TR3PA (95%) and TM1PM (94%). The shortest LC50 at 72 hours and LT50 at 10000 mg/L concentration was observed in TR3CH (1391 mg/L; 24.32 hours), TR3PM (1516 mg/L; 27.50 hours), TR3AC (1644 mg/L; 31.30 hours), TR3PA (1766 mg/L; 30.83 hours) and TM1PM (1832 mg/L; 34.43 hours). The highest repellency percentage was also recorded for TR3CH (76%) followed by TR3PM (73%), TR3PA (69%), TR3AC (64%) and TM1PM (64%). These formulations were further evaluated for their efficacy against cotton aphid in glasshouse and results revealed that lowest LC50 (1480 mg/L) after 120 hours and shortest LT50 (29.1 hours) at 20000 mg/L concentration was recorded for TR3CH. TR3CH (25% Termul 1284, 5% rapeseed oil with C. hirta as an active ingredient) nano-emulsion formulation overall performed better than all other tested nano- emulsion formulations, therefore, it could be considered as an eco-friendly alternative approach in pesticides technology.